Ion-exchanged zeolite P as a nanostructured catalyst for biodiesel production - Aqeel Al-Ani; Natalie E. Mordvinova; Oleg I. Lebedev; Andrei Y. Khodakov; Vladimir Zholobenko (Energy Reports, 2019)
Nano-crystalline synthetic gismondine modified via cation exchange has been utilised as a highly active and selective catalyst for the production of biofuel. In comparison with low silica zeolites FAU and LTA, K-form of gismondine, based on the maximum aluminium P (MAP) zeolite, exhibited a significant improvement in catalytic performance in the methanolysis of bio-oil, which can be attributed to its nano-particle morphology and high basicity associated with the high Al content and high degree of ion exchange, as demonstrated by the TEM, XRD, TGA, NMR, XPS and CO2-TPD studies. To the best of our knowledge, this is the first report on a successful catalytic application of basic K-MAP zeolite.
Keywords: 330; Transesterification; Basic sites; Nanostructured catalysts; Synthetic gismondine; Zeolites